Freire’s Pedagogy of Freedom: Its Contribution to the Development of Ethical Teacher Professionality through the Implementation of the New Zealand Curriculum - Benadé, Leon (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2010)
This paper takes lessons and directions from Paulo Freire’s Pedagogy of Freedom (1998) that both inform the theme of Dialogue and Difference and a particular conception of ethical teacher professionality. Freire’s vision of teachers and teaching challenges managerialist notions of teachers as dispassionate, data-driven objects of bureaucratic policy, aligned to a sanitised list of features that make up ‘the effective teacher’. This representation of teachers is unlikely to motivate or prepare teachers in the future to be critical thinking ethical professionals. An alternative conception of the teaching professional is required, and one is presented here which has strong links to Pedagogy of Freedom in particular, and critical pedagogy more generally. Expressed as ‘ethical teacher professionality’, this account suggests a broader approach to the role of teacher than provided by notions such as ‘satisfactory teacher dimensions’ or ‘characteristics of quality teaching’.The New Zealand Curriculum (Ministry of Education, 2007) is a policy text whose understanding of teachers is informed by such notions. New Zealand schools engaged in a process of preparation in 2008 and 2009 for full implementation of this revised national curriculum in 2010. The scope of these revisions, expectations of teachers, and the requirement that this implementation be school-based (rather than centrally prescribed) mean that in essence this curriculum goes well beyond a mere revision. Further, as a product of early-21st century education reform which seemingly gives schools, teachers and communities greater flexibility, there are lessons that could be relevant internationally. As a fundamentally new approach to policy, implementation of the New Zealand Curriculum could significantly alter how teachers see and approach their work.